Update on endoscopic treatment of Barrett's oesophagus and Barrett's oesophagus–related neoplasia. (July 2020) - Pech, Oliver; Alqahtani, Saleh A.
Endoscopic therapy of early Barrett's oesophagus–related neoplasia is the treatment of choice for low-grade-dysplasia, high-grade dysplasia and mucosal Barrett's cancer. Low-grade-dysplasia without any visible lesion should be ablated, preferably with radiofrequency ablation. In cases with the presence of a visible lesion, high-grade dysplasia and early Barrett's adenocarcinoma, endoscopic resection techniques like multiband ligation endoscopic resection or endoscopic submucosal dissection should be applied. After complete resection of all visible neoplastic lesions, ablation of the remaining Barrett's oesophagus should be performed to prevent recurrence. Ablation techniques available are radiofrequency ablation, argon plasma coagulation and cryoablation.